Dengue: The break-bone fever outbreak in Kerala, India - Banerjee, Indrajit (Nepal Journal of Epidemiology, 2017)
Recently a shocking intensification of dengue cases has also been seen in India in 2017. The common serotype of Dengue Asian genotype of DENV-1 was detected in South India in 2012.